When work is not enough : state and federal policies to support needy workers - Stoker, Robert Phillip, 1954- (Brookings Institution Press, 2006)
"Examines a broad range of state and federal programs providing cash or in-kind benefits to low-wage workers, low-income families, and families making the transition from welfare to work to assess the ability of the work support system to lead to self-sufficiency"--Provided by publisher